THE IMPACT OF SELF-MANAGEMENT ON RESILIENCE, STRESS, AND MEANARTERIAL PRESSURE IN HYPERTENSION PATIENTS - Faisal Amir; Lantin Sulistyorini; Suraying; Mohamad Nur; Sitti Sulaihah; Mohammad Lutfi (NurseLine Journal, 2025)
Background: Hypertension is a chronic disease that requires self-management skills to enhance resilience, reduce psychological distress, maintain optimal blood pressure control. Objective: To investigate relationship between self-management, resilience, psychological stress, mean arterial pressure in patients with hypertension. Methods: A cross-sectional correlational design. 62 respondents were selected using a random sampling from a population of 89 patients. The instruments used Hypertension Self-Management Behaviour Questionnaire, the Connor-Davidson Resilience Scale, and Perceived Psychological Stress Scale, while MAP was measured using a calibrated digital sphygmomanometer. Data were analyzed using ordinal logistic regression with a significance level (Alfa) of 0.05. Results: Selfmanagement, resilience, psychological stress simultaneously influenced blood pressure of hypertensive patients (p 0.006, <0.05). Parameter estimation analysis revealed that self-management (Beta -0.850; p 0.005), resilience (Beta -1.420; p 0.002), stress (Beta 0.520; p 0.004). All independent variables significantly influence dependent variable, although variance explained 19.6% (R² = 0.196), indicates a relatively low contribution. Conclusion: Improved self-management, resilience, stress management are significantly associated with blood pressure stability in hypertensive patients.These components can serve as a strategic complement to care, both at home and in community.